Flavonoids from the leaves and heartwoods of Artocarpus lowii King and their bioactivities - Abdullah, Siti Awanis (Taylor and Francis Inc., 2017)
A new dihydrochalcone, 2′,4′-dihydroxy-3,4-(2″,2″-dimethylchromeno)-3′-prenyldihydrochalcone (1) together with 4-hydroxyonchocarpin (2), isobavachalcone (3), 4′,5-dihydroxy-6,7-(2,2-dimethylpyrano)-2′-methoxy-8-γ,γ-dimethylallyflavone (4), artocarpin (5) and cycloheterophyllin (6) were successfully isolated from the leaves and heartwoods of Artocarpus lowii King (Moraceae). The structures of these compounds were fully characterised using spectroscopic methods and by direct comparison with published data. These compounds were tested for their antioxidant and tyrosinase inhibitory activities. Compound (1) displayed moderate antioxidant activity towards DPPH and tyrosinase inhibitory activities with SC50 value of 223.8 μM and IC50 value of 722.5 μM, respectively. Among the isolated compounds, cycloheterophyllin (6) showed the most potential antioxidant activity with SC50 value of 320.0 and 102.8 μM for ABTS and DPPH radicals scavenging activities, respectively, and also exhibited highest FRAP equivalent value of 4.7 ± 0.09 mM. Compound (6) showed tyrosinase inhibitory activity with the IC50 value of 104.6 μM.